Pengaruh Kompetensi dan Insentif Terhadap Prestasi Kerja Karyawan PT. Kartika Swarna Dwipa - Selywati Selywati; Syawaluddin Syawaluddin; Aidil Putra; Thomas Sumarsan Sumarsan Goh (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2023)
Kartika Swarna Dwipa is a company engaged in the marketing of Tupperware products. Employee work performance is starting to experience a decline which is indicated by the low morale of employees in completing work. Low competence because employees tend to only graduate from high school and have not been given training. The provision of incentives in fact has problems such as commissions and overtime incentives that are not as promised. This research uses quantitative descriptive research. The total population in the study was 39 employees with a sampling technique using saturated samples. Simultaneously there is a significant influence between the variables of competence and incentives on the work performance of employees of PT. Kartika Swarna Dwipa. While partially, it was found that the competence variable had a significant effect on the work performance of PT. Kartika Swarna Dwipa. Partially, it was found that the incentive variable had a significant effect on the work performance of PT. Kartika Swarna Dwipa. The results of this study indicate that the competence variable has more influence than incentive on the work performance of PT. Kartika Swarna Dwipa.